Global food security - Isabel Teichmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
According to the current report on the Millennium Development Goals (UN 2015), the share of undernourished people living in the developing world has fallen from 23.3% in 1990-1992 to 12.9% in 2014-2016 (projection). Despite this progress towards global food security, about 795 million people worldwide (or 780 million people in developing regions) will remain undernourished in 2014-2016 (UN 2015). Put differently, more than 10% of the world population still suffers from chronic hunger (FAO et al. 2015). Moreover, globally, one in seven children under age five are projected to be underweight in 2015 and one in four were stunted in 2013, i.e. had inadequate height for their age (UN 2015) - not only causing current hardship and pain but also leading to adverse long-term effects (see Lehmann-Uschner 2015). Against this background, global food security will feature prominently in the emerging post-2015 development agenda, such as the Sustainable Development Goals (UN 2015). Food security is defined as a status in which "all people, at all times, have physical and economic access to sufficient, safe and nutritious food to meet their dietary needs and food preferences for an active and healthy life" (FAO 1996: Paragraph 1). The main challenges to global food security in the medium- to long-term range from a growing world population to more resource-intensive diets, bioenergy generation and climate change. Already today, these developments account at least partly for the current rise in agricultural commodity prices. In addition to the fight against poverty, proposed solutions to meet the challenges include a sustainable intensification of agricultural production, reductions in yield losses and food wastes, open trade regimes, emission-saving agricultural practices and shifts in consumer preferences towards more sustainable demand patterns.
Keywords: 330